Sites of exchange : European crossroads and faultlines - Ascari, Maurizio; Corrado, Adriana (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2006)
Crossing borders - both physically and imaginatively - is part of our 'nomadic' postmodern identity, but transcultural and transnational exchanges have also played a major role in the centuries-long processes of hybridisation that helped to fashion the vast geographic, political and imaginative container of diversity we call Europe. This volume gathers together the work of scholars from several European countries in an attempt to encourage a collective reflection upon historical - and often 'mythical' - locations and landscapes, as well as upon the thresholds and faultlines that unite or separ.